Age-related iron accumulation and demyelination in the basal ganglia are closely related to verbal memory and executive functioning - Davina Biel (Nature Portfolio, 2021)
Abstract Age-related cognitive decline has been linked to alterations of the dopaminergic system and its subcortical trajectories. Recent work suggests a critical role of iron accumulation within the basal ganglia (BG) in verbal memory performance, and increased iron levels have been related to demyelination. However, the specificity of age-related iron increases with respect to cognitive functions remains unclear. Therefore, we investigated the interplay of age, cognitive performance, and structural integrity of the BG. In total, 79 healthy older participants underwent a broad cognitive assessment (fluid and crystallized intelligence, verbal and numeric memory, processing speed, executive functions) and structural MRI. As expected, performance in most cognitive tests had a negative relationship with age. Moreover, BG grey matter volume and magnetization transfer (MT, indicative of myelin) decreased, and R2* (indicative of iron) increased with age. Importantly, R2* and demyelination negatively correlated with verbal memory and executive functions. Within the SN/VTA, age correlated negatively with MT, but there was no clear evidence in favor of a relationship between behavior and R2* or MT. Our results suggest that age-related increases in iron and demyelination within the BG, which are part of a fronto-striatal network, not only impact on verbal memory but also executive functions.